Design of 2D skyrmionic metamaterials through controlled assembly - Qichen Xu; Zhuanglin Shen; Alexander Edström; I. P. Miranda; Zhiwei Lu; Anders Bergman; Danny Thonig; Wanjian Yin; Olle Eriksson; Anna Delin (npj Computational Materials)
Abstract Despite extensive research on magnetic skyrmions and antiskyrmions, a significant challenge remains in crafting nontrivial high-order skyrmionic textures with varying, or even tailor-made, topologies. We address this challenge, by focusing on a construction pathway of skyrmionic metamaterials within a monolayer thin film and suggest several skyrmionic metamaterials that are surprisingly stable, i.e., long-lived, due to a self-stabilization mechanism. This makes these new textures promising for applications. Central to our approach is the concept of ’simulated controlled assembly’, in short, a protocol inspired by ’click chemistry’ that allows for positioning topological magnetic structures where one likes, and then allowing for energy minimization to elucidate the stability. Utilizing high-throughput atomistic-spin-dynamic simulations alongside state-of-the-art AI-driven tools, we have isolated skyrmions (topological charge Q = 1), antiskyrmions (Q = − 1), and skyrmionium (Q = 0). These entities serve as foundational ’skyrmionic building blocks’ to form the here-reported intricate textures. In this work, two key contributions are introduced to the field of skyrmionic systems. First, we present a novel combination of atomistic spin dynamics simulations and controlled assembly protocols for the stabilization and investigation of new topological magnets. Second, using the aforementioned methods we report on the discovery of skyrmionic metamaterials.